If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4x = -7 Solving 9 + -4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = -7 + -9 -4x = -7 + -9 Combine like terms: -7 + -9 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| (x-4)(x-3)=8 | | 4x^2+7=9 | | 2X+3Y=132 | | 4a+13=33 | | -20x^2-7x+3=0 | | 17x-5=12x+6 | | 4x-12y=24 | | 3z-4=5z-2 | | 15x^2=25x | | 4x-12y=18 | | w-5=14 | | v=2a+3b+c | | 4x+9Y=11 | | 2w+4=25+4w | | 14x=36 | | ln(x+1)-ln(x)=2 | | 7-2x=25 | | ln(-7x+5)=12.25 | | x+3x-34=180 | | 5x+18y=16 | | 12*31= | | 5x-15y=20 | | 4a+28= | | 2x-1*x*x+8*2x+5*x-3= | | X^2+16-8x=0 | | (2x+3)-(x+1)=(x+1) | | x+5*x-3= | | 9x-84=4x-14 | | 3(7t-14)=-21t+42 | | 2x+5*2x+5= | | 159-4x=32x+23 | | (2x-y)(4x^2-y^2)=a |